"A Liberation of Powers": Agency and Education for Democracy. Issue 1 (April 2016) - Boyte, Harry C.; Finders, Margaret J.
Abstract: In this essay Harry Boyte and Margaret Finders argue that addressing the "shrinkage" of education and democracy requires acting politically to reclaim and augment Deweyan agency‐focused concepts of democracy and education. Looking at agency from the vantage of civic studies, which advances a politics of agency — a citizen politics that is different from ideological politics — and citizens as cocreators of political communities, Boyte and Finders explore the technocratic trends that have eclipsed agency. These disempower educators, students, and communities. Using the case study of the youth empowerment initiative Public Achievement and its translation into the Special Education Program and partnerships of Augsburg College, the authors conclude with an examination of how agentic practices have survived in "shadow spaces" in schools, how such spaces might be turned into "free spaces" for democratic change, and how teacher education needs to prepare "citizen teachers" as well as promoting pedagogies of empowerment. These suggest grounds for a movement of hope and democratic change.